Anti-High-Density Lipoprotein Antibodies and Antioxidant Dysfunction in Immune-Driven Diseases - Rodríguez-Carrio, Javier; Mozo, Lourdes; López, Patricia; Nikiphorou, Elena; Suárez, Ana (Frontiers in Medicine, 2018)
IIntroduction: Impaired HDL levels and antioxidant functionality of HDL, mainly attributed to a decreased paraoxonase-1 (PON1) functionality, have been described in autoimmune conditions. In this setting, a role for humoral response in cardiovascular (CV) disease is emerging. This study evaluates the role of IgG antibodies against HDL and disease-related autoantibodies on HDL dysfunction in immune-driven diseases. Methods: Serum IgG anti-HDL antibodies, PON1 activity and total antioxidant capacity (TAC) were quantified in 381 patients with different immune-driven diseases (18 MCTD, 35 pSS, 38 SSc, 33 AAV, 60 DM1, 29 autoimmune B12 deficiency/Pernicious Anemia, 29 Primary Biliary Cirrhosis, 46 IBD/Crohn, 54 IBD/UC and 39 coeliac disease –CD–) and 138 healthy controls. Results: IgG anti-HDL antibodies were increased in MCTD, pSS, AAV and IBD (Crohn and UC), even after correcting for total IgG levels, but not in organ-specific autoimmune diseases. Anti-HDL antibodies were negatively associated with PON1 activity in MCTD (r=-0.767, p<0.001) and AAV (r=-0.478, p=0.005), whereas both anti-HDL and ANCA levels were related to an impaired PON1 activity and TAC in IBD/UC. In SSc, anti-centromere antibodies correlated PON1 activity. ASCA levels were negatively associated with PON1 activity (r=-0.257, p=0.012) and PON1/TAC ratio (r=-0.261, p=0.009) in IBD/Crohn. HDL dysfunction in CD was only related to anti-transglutaminase levels. Conclusions: IgG anti-HDL antibodies and HDL dysfunction are common hallmarks of systemic autoimmunity. Anti-HDL and disease-related autoantibodies account for the HDL antioxidant dysfunction in immune-driven conditions, mainly in systemic autoimmune disorders.